Identification Of Freshness Level Of Mackerel (Rastrelliger Kanagurta) In Tanjungsari Market, Sumedang Regency. - Junianto, Junianto; Muhikun, Bahrun; Sigar, Yosia Petersen; Hanifa, Faiza; Putra, M Zidan; kusumah, Tiranti damayanti (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Fresh fish or wet fish is fish that has not been or is not preserved with anythingexcept simply cooled with ice. Fish is said to have maximum freshness if its properties arestill the same as live fish, both in appearance, taste, and texture. The level of freshness offish can be identified or assessed organoleptically. Human senses are instruments used inVolume 5, Number 2, June 2025https://journal.unram.ac.id/index.php/jmai/index. E-ISSN : 2798-055331organoleptic tests, which include sight, smell, taste, touch and hearing. This study aims todetermine the level of freshness of mackerel and fresh fish at Tanjung Sari Marketorganoleptically. This research method is by taking mackerel samples and at 10.00 WIB,then its freshness is identified qualitatively through organoleptic observations. Samplingwas carried out on May 20, 2025. Organoleptic assessment is the most widely usedmethod in determining signs of fish freshness because it is easier and faster to do, doesnot require a lot of equipment, and does not require a laboratory. Subjective(organoleptic) determination of fish quality decline is carried out using a score sheet thathas been set by the National Standardization Agency SNI 01-2346-2006 (BSN 2006) andusing 5 (five) panelists. The parameters observed are the condition of the eyes, gills,mucus, meat, odor, and texture. For organoleptic observations, a detailed assessment (seethe score sheet table) is carried out on the fish in the range of values 1 to 9. In theorganoleptic testing of test fish sold in retail by traders at Tanjungsari market, the valuesobtained ranged from 7-8, which means that the fish still has good quality and meets therequirements set by SNI (2006), namely the standard for fresh fish for organoleptictesting, which is a minimum of 7.